Predicting acute lung injury in infants with congenital heart disease after cardiopulmonary bypass by gut microbiota - Jiang, Lan; Cun, Yueshuang; Wang, Qiang; Wu, Kede; Hu, Menglong; Wu, Zhen; Zhu, Tianyi; Yang, Zhaocong; Patel, Nishant; Cai, Xinyu; Qi, Jirong; Mo, Xuming (Frontiers in Immunology, 2024)
Background: Acute lung injury (ALI) is a serious and common complication that occurs in children with congenital heart disease after cardiopulmonary bypass (CPB) surgery, leading to higher mortality rates and poorer prognosis. Currently, there is no reliable predictive strategy for CPB-associated lung injury (CPB-ALI) in infants. Certain characteristics of the gut microbiota could potentially serve as biomarkers for predicting the development of CPB-ALI.We conducted 16S rRNA sequencing to analyze the characteristics of the intestinal microbiota in healthy controls and infants with CHD admitted to the hospital. The CHD infants were divided into CPB-ALI and non-ALI (CPB-NALI) groups based on postoperative outcomes. Bacterial functional pathway prediction analysis was performed using PIRCUSt2, and the gut microbiota composition associated with immune status was determined with heatmap. Random forest regression models and ROC curves were utilized to predict the occurrence of CPB-ALI.Results: Our study revealed significantly different microbiota compositions among three groups (CON, CPB-ALI, and CPB-NALI). The microbiota diversity was low in the CPB-ALI group with high pathogen abundance and significant decrease in Bacteroides, while the opposite was observed in the CPB-NALI group. The microbiota dysbiosis index was high in the CPB-ALI group, with its dominant microbiota significantly associated with multiple metabolic pathways. Additionally, CPB-ALI patients showed high levels of inflammatory cytokines IL-8 and HMGB1 in their serum, with high expression of IL-8 being associated with Enterobacteriaceae. Further correlation analysis showed that the differences in gut bacterial taxonomy were related to the occurrence of ALI, length of stay in the cardiac care unit, and ventilation time. It is noteworthy that Escherichia Shigella performed best in distinguishing CPB-ALI patients from non-ALI patients. Conclusions: Our study suggests that postoperative ALI patients have distinct gut microbiota upon admission compared to non-ALI patients after surgery. Dysbiosis of the gut microbiota may potentially impact the progression of ALI through metabolic pathways, quorum sensing, and the levels of inflammatory factors expressed in the serum. Escherichia Shigella represents a potential predictive factor for the occurrence of ALI in CHD infants after surgery.